An assessment of the capability of the Municipal Planning and Development Offices of the Province of Aklan - Miroy, Ma.Mujane Begonia C. (1995)
The study covered 15 Municipal Planning and Development Offices in the province of Aklan. Using a survey questionnaire for primary data collection and on-site interview for data validation, the study aimed at determining and assessing the characteristics of MPDO personnel and physical facilities. Also, it aimed at establishing the relationship of the personnel and physical resources to office performance as indicated by: efficacy, effectiveness, productivity, responsiveness, and timeliness. The 15 MPDOs had a composite of 53 employees -- 48 permanent and 5 casuals. Average number of employees was 3.2 permanent personnel per office. The permanent employees occupied varied positions, 15 of which were MPDCs. These employees possessed the educational competence to perform office functions. Trainings attended averaged 5.93 training areas per office; only 40.00 of subject offices possessed the technical competence gained from trainings. Eleven MPDOs had offices of their own; most do not have enough office, communication and transportation facilities to support their office functions. The Ø coefficient of correlations was used to determine the relationship between each office resource and performance. The correlation of each resource to performance were found to be as follows: Number: Ø = 0.14, a negligible correlation; Education: Ø = 0.60, a moderately high correlation; Office & Equipment: Ø = 0.17, a negligible correlation; Communication support: Ø = 0.42, a moderate correlation; and Transportation support: Ø = 0.09, a negligible correlation. Attributable factors for the lack of office resource include, among others: lack of LGU funds, lack of budgetary support, lack of political will, and political interference.
[Research Paper} (PM 299). -- Iloilo City : UOV-CM, October 1995.